Experimental Evaluation of Conical Tank Level Control Using Fractional Pid - Travieso-Torres, J (IEEE Computer Society, 2016)
In this paper, experimental results on the conical tank level control are presented. PI/PID controllers of integer order (IO) as well as of fractional order (FO) are studied and compared. The tuning parameters are obtained first by using Root Locus (RL) method, for comparison purposes. Next, Particle Swarm Optimization (PSO) is employed to determine the controllers parameters using as fitness function the integral of the absolute value of tracking error (IAE). From the experimental results it is concluded that PI/FOPI are the controllers presenting the lowest IAE indexes, whereas PID/FOPID controllers present the lowest energy consumption by the control signal. © 2016 IEEE.